Effects of chronic clozapine administration on markers of arachidonic acid cascade and synaptic integrity in rat brain - Kim, Hyung-Wook (2012)
The mode of action of clozapine, an atypical antipsychotic approved for treating schizophrenia and bipolar disorder (BD) mania, remains unclear. We tested for overlap with the actions of the mood stabilizers, lithium, carbamazepine and valproate, which downregulate arachidonic acid (AA) cascade markers in rat brain and upregulate BDNF. AA cascade markers are upregulated in the postmortem BD brain in association with neuroinflammation and synaptic loss, while BDNF is decreased. Rats were injected intraperitoneally with a therapeutically relevant dose of clozapine (10 mg/kg/day) or with saline for 30 days, and AA cascade and synaptic markers and BDNF were measured in the brain. Compared with saline-injected rats, chronic clozapine increased brain activity, mRNA and protein levels of docosahexaenoic acid (DHA)-selective calcium-independent phospholipase A(2) type VIA (iPLA(2)), mRNA and protein levels of BDNF and of the postsynaptic marker, drebrin, while decreasing cyclooxygenase (COX) activity and concentration of prostaglandin E(2) (PGE(2)), a proinflammatory AA metabolite. Activity and expression of AA-selective calcium-dependent cytosolic cPLA(2) type IVA and of secretory sPLA(2) Type II were unchanged. These results show overlap with effects of mood stabilizers with regard to downregulation of COX activity and PGE(2) and to increased BDNF, and suggest a common action against the reported neuropathology of BD. Additionally, the increased iPLA(2) expression following clozapine suggests increased production of anti-inflammatory DHA metabolites, consistent with reports that dietary n-3 polyunsaturated fatty acid supplementation is beneficial in BD.